Beyond the Watchdog: Exploring Sousveillance as an Alternative Form of Media Oversight - Puji Rianto; Ade Irma Sukmawati; Dian Dwi Anisa (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung Sunan Gunung Djati Bandung, 2025)
Empirical research indicates that the mainstream media in Indonesia frequently fail to serve as effective watchdogs. In contrast, social media platforms facilitate digital democracy by enabling citizens to oversee power structures, although they also increase opportunities for government surveillance. This study aims to assess whether sousveillance can serve as an alternative mechanism for monitoring power when mainstream media do not fulfill their watchdog role by analyzing trends in mainstream media, Twitter, and citizen sousveillance. A mixed-methods approach is employed. The quantitative method utilizes Natural Language Processing (NLP) and the Naive Bayes sentiment analysis technique, while qualitative content analysis enriches the findings. The results demonstrate that news coverage in mainstream media outlets (Jawa Post, Kompas, and CNN Indonesia) failed to fulfill the watchdog function, as reporting was predominantly positive toward the government and its supporters, and hostile toward NGOs and groups critical of the government. A similar trend is observed on Twitter. However, analysis of sousveillance practices reveals that, although sousveillance does not directly influence policy change, it contributes to intermedia agenda-setting and can function as an alternative form of oversight. These findings highlight the significance of sousveillance as a form of citizen oversight, particularly in contexts where democratic institutions are in decline.